The Implementation of Culturally Responsive Teaching (CRT) Approach to Improve Learning Outcomes and Learning Motivation of Grade XI.3 Students at SMA Negeri 1 Palembang - Nuraini, Nuraini; Camellia, Camellia; Maimun, Maimun (PPG IKIP Siliwangi, 2025)
This study aims to improve students’ learning outcomes and learning motivation in the subject of Pancasila Education through the implementation of the Culturally Responsive Teaching (CRT) approach. CRT is a teaching approach that integrates students’ cultural backgrounds into the learning material, making the learning process more relevant and inclusive. This research is a type of Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of the research were 38 students from class XI of SMA Negeri 1 Palembang in the 2025/2026 academic year. Data were collected through observation and tests. The results of the study showed an improvement in students' learning outcomes: in Cycle 1, the average score was 79.05 with a classical completeness of 65%, while in Cycle 2, the average score increased to 96.36 with a classical completeness of 94%. Regarding learning motivation, in Cycle 1 the average was 73%, categorized as high, whereas in Cycle 2 it increased to 95%, categorized as very high. These results indicate that the implementation of the Culturally Responsive Teaching (CRT) approach can enhance students.